Direct Nucleophilic Addition to N‐Alkoxyamides. Issue 2 (14th November 2012) - Yanagita, Yuta; Nakamura, Hugh; Shirokane, Kenji; Kurosaki, Yusuke; Sato, Takaaki; Chida, Noritaka
Abstract While the synthesis of amide bonds is now one of the most reliable organic reactions, functionalization of amide carbonyl groups has been a long‐standing issue due to their high stability. As an ongoing program aimed at practical transformation of amides, we developed a direct nucleophilic addition to N‐alkoxyamides to access multisubstituted amines. The reaction enabled installation of two different functional groups to amide carbonyl groups in one pot. The N‐alkoxy group played important roles in this reaction. First, it removed the requirement for an extra preactivation step prior to nucleophilic addition to activate inert amide carbonyl groups. Second, the N‐alkoxy group formed a five‐membered chelated complex after the first nucleophilic addition, resulting in suppression of an extra addition of the first nucleophile. While diisobutylaluminum hydride (DIBAL‐H) and organolithium reagents were suitable as the first nucleophile, allylation, cyanation, and vinylation were possible in the second addition including inter‐ and intramolecular reactions. The yields were generally high, even in the synthesis of sterically hindered α‐trisubstituted amines. The reaction exhibited wide substrate scope, including acyclic amides, five‐ and six‐membered lactams, and macrolactams.